Experimental type 2 diabetes mellitus and acetaminophen toxic lesions: glutathione system indices changes - Furka, Olga; Ivanusa, Iryna; Mykhalkiv, Mariya; Klishch, Ivan (Journal of Education, Health and Sport, 2017)
Background. The goal of the research was to study the effect of acetaminophen on major glutathione part of antioxidant system indices in liver homogenate of rats with type 2 diabetes mellitus in time dynamics. Materials and methods. We conducted two series of experiments. In the first series toxic lesion was caused by a single intragastric administration of acetaminophen suspension in 2 % starch solution to animals in a dose of 1250 mg/kg (1/2 LD50). In the second series the suspension of acetaminophen in 2 % starch solution in a dose of 55 mg/kg was given, which corresponds to the highest therapeutic dose during 7 days. Non-genetic form of experimental type 2 diabetes mellitus was modeled by Islam S., Choi H. method (2007). Activity of glutathione peroxidase (GPx) and glutathione reductase (GR), and contents of reduced glutathione (GSH) were determined in liver homogenate. Results. The obtained results have shown that GR and GPx activity actively decreased after acetaminophen administration in higher therapeutic doses to rats with type 2 DM. However, the changes were less pronounced than in rats with type 2 DM and acute acetaminophen toxic lesions. Conclusion. Results of the research have shown that acetaminophen administration to rats with type 2 DM causes a significant violation of compensatory mechanisms, especially of the enzyme and nonenzyme parts of antioxidant system.